Neural Repair in Stroke. Issue 9 (September 2019) - Toman, Nikolas G.; Grande, Andrew W.; Low, Walter C.
This article reviews the progress that has been made in the development of cell therapies for the repair of nervous system damage caused by strokes, since the first report on the use of cell transplants in animal models of ischemic brain injury in 1988. At that time neural progenitor cells derived from fetal brain tissue were used as sources of cells to replace specific subsets of neuronal cells that were lost in various regions of the brain following experimentally induced strokes. Since 1988, cells from other sources, such as embryonic stem cells and inducible pluripotent stem cells, have been investigated for their ability to replace neuronal cells and repair the damaged brain. Most recently, mesenchymal stem cells and cord blood stem cells have been studied for the ability to modulate the immune system and ameliorate the neuropathology and neurological deficits associated with experimental stroke. The preclinical investigation of different cell therapy approaches for treating stroke during the past three decades has now led to many ongoing clinical trials, with the clinical evaluation of stem cell therapies for stroke now involving global participants.